A comparative study of ultrasonic-assisted methods to synthesise spinel (CoAl2O4) nanoparticles - Dumanli, Fatma Tugce Senberber; Derun, Emek Moroydor (ELSEVIER SCI LTD, 2022)
In this study, a spinel form of cobalt aluminate (CoAl2O4) was successfully synthesized using different experimental procedures assisted by ultrasonics. The effects of ultrasonic treatment with co-precipitation and hydrothermal experimental methods were compared with traditional techniques. The results indicated that enhanced chromatic features resulted from the experimental procedures modified by ultrasonic treatment. In chromatic analyses, the lowest b* value of -47.19 was observed in the sample synthesized by the ultrasonic-assisted coprecipitation method. This synthesized phase was identified as Spinel with the chemical formula of CoAl2O4 according to Powder Diffraction File number (PDF no.) 01-0820-2251 from XRD analyses. The optimum samples were determined to be UC-8 and UH-9 for the modified methods. For these samples the particle sizes were measured between 62 and 83 nm, whereas crystallite sizes were estimated to be in the range from 33 to 43 nm. The thermal analyses results proved the stability of the sample structure up to 1000 degrees C.
Keywords: Co-precipitation synthesis; Hydrothermal synthesis; Ultrasonic treatment; Spinel; OPTICAL-PROPERTIES; BLUE; COBALT; NANOPIGMENTS; PERFORMANCE; Materials Science